Keynote Address: Building excellence in higher education: Singapore's experience - DE MEYER, Arnoud (Institutional Knowledge at Singapore Management University, 2022)
Using the research done on higher education in Singapore, he identified some drivers of the success of higher education: a system that is fit for purpose, a signification investment in R&D, good governance, active learning from overseas partners, and flexibility in implementation. The future challenges that higher education could face included: the role of technology, the changing nature of work, jobs and careers, the challenge of life-long learning, and translating research into innovation.